DTI-ALPS index-assessed glymphatic dysfunction mediates Alzheimer's cognitive decline via amyloid-β-dependent pathways: multimodal PET/MRI study. - Zhang, Yan; Huang, Gan; Geng, Jieli; Li, Xia; Xin, Mei; Yuan, Peizhe; Wang, Yue; Xu, Qun; Wang, Gang; Huang, Gang; Liu, Jianjun; Zhang, Chenpeng (European Journal of Nuclear Medicine & Molecular Imaging, 2025)
Purpose: The role of glymphatic dysfunction in Alzheimer's disease (AD), as measured by diffusion tensor imaging along perivascular spaces (DTI-ALPS) indexing of perivascular function, its progression, and its interaction with amyloid-β (Aβ) and tau proteins, remains controversial. To investigate whether the DTI-ALPS index mediates AD-related cognitive decline through Aβ/tau-dependent pathways using tri-tracer PET/MRI. Methods: This retrospective study (2021–2024) analyzed 140 participants (median age 69.00 [61.00, 74.00] years; 84 women), including 99 with AD (37 early-onset [EOAD], 62 late-onset [LOAD]), 35 with mild cognitive impairment (MCI), and 6 with subjective cognitive decline (SCD). All participants underwent simultaneous [1⁸F] Florbetapir (Aβ), [1⁸F] PI-2620(tau), and [1⁸F] FDG PET/MRI with DTI-ALPS indexing for glymphatic function quantification. Causal mediation analysis was used to assess the relationships between biomarkers (P < 0.05). Results: The ALPS index progressively decreased across clinical stages (SCD: 1.51 ± 0.08 vs. MCI: 1.37 ± 0.13 vs. AD: 1.32 ± 0.14; P = 0.001), correlating with higher Aβ-PET (r = − 0.31, P < 0.001), tau-PET (ρ = − 0.18, P = 0.035), and FDG-PET scores (ρ = − 0.22, P = 0.008). Aβ-PET fully mediated the ALPS effects on FDG-PET (β = − 0.14, P = 0.002) and cognition (β = 0.12 ~ 0.14, P < 0.01), independent of tau (P > 0.05). The Aβ-negative subgroups showed correlations with ALPS-age (r = − 0.48, P = 0.007), ALPS-education (r = 0.39, P = 0.035), and ALPS-cognition (MoCA: r = 0.62, P < 0.001). The Aβ-positive subgroups revealed inverse ALPS-Aβ associations (ρ = − 0.27, P = 0.010; age/education-adjusted ρ = − 0.24, P = 0.022) alongside positive adjusted correlations with cognition (MMSE: ρ = 0.28, P = 0.009). EOAD exhibited distinct ALPS-cognition relationships compared to LOAD (MMSE: r = − 0.39, P = 0.016 vs. ρ = − 0.06, P = 0.620). Conclusion: DTI-ALPS quantifies glymphatic dysfunction driving AD progression predominantly through Aβ-dependent pathways, with EOAD demonstrating distinct neuroimaging-cognition relationships compared to LOAD.